The role of regional atmospheric stability in high-pm10 concentration episodes in Miercurea Ciuc (Harghita) - Szép, R.; Matyas, Laszlo (Universitatea de Nord din Baia Mare, 2014)
The conditions of accumulation of the particulate matter with diameter <10μm - PM10 in 2 episodes of thermal inversion from the Ciuc Depression were studied, with focus on the intradiurnal variation. The data taken from the regional monitoring station of the air quality from the Jigodin-Ciuc have been used. In accordance to the observations made in the Venice-Mestre area, when the intradiurnal variation of PM10 values is greater than the daily average, static stability has an important role in the accumulation of PM10, without having a linear behaviour. A relative increase of the static stability in Brunt Väisälä terms is enough to produce increases over the daily limit values (50μg/m3) of the PM10. The diurnal behaviour is highlighted by a maximum, respectively a minimum value; the maximum value occurs especially in the late afternoon and in the early evening, and the minimum values occur especially in the early morning. If we report the maximum and minimum values to the diurnal cycle of the atmospheric pressure variation, we can notice that these values fit to the time limit periods between them. If we strictly refer to the distribution of the minimum and maximum values, as it’s well-known, taking into account the values of the static stability, we can notice that the increased values of the static stability induce maximum values of PM10, while its low values determine an increase of the frequency of minimum diurnal values of PM10.